Analisis Hukum Terhadap Pencegahan Kasus Deepfake Serta Perlindungan Hukum Terhadap Korban - Respati, Adnasohn Aqilla; Setyarini, Astri Dewi; Parlagutan, Dodi; Rafli, Muhammad; Mahendra, Rayhan Syahbana; Nugroho, Andriyanto Adhi (Media Hukum Indonesia (MHI), 2024)
This research will examine various legal aspects related to Deepfake Porn, including the role of law in protecting individual privacy, copyright, and cyber security. In addition, this research will also explore the potential for public awareness education as a preventative measure by increasing public understanding of the risks of Deepfakes and how to protect themselves from possible misuse of this technology. The research method that can be used to analyze efforts to prevent deepfake pornography and educate public awareness in the digital environment is the normative juridical research method. The steps in this method include identifying the legal problem to be researched, collecting data through searching regulations and literature related to the problem. Protection of personal data in the use of Artificial Intelligence (AI) technology is very important to avoid threats such as deepfake videos. Personal data, including personal photos, must be legally protected. Privacy is divided into three types: Physical Privacy, Information Privacy, and Organizational Privacy, which includes protection of individual communications, behavior and identity. In Europe, citizens can exercise the "right to be forgotten" (RTBF) right to delete personal information from the internet, as experienced by Mario Costeja Gonzalez in 2010. The EU updated the RTBF rules in the GDPR since May 2018. Indonesia also has a similar concept in the ITE Law Article 26 paragraphs (3) and (4), although the implementation is different and faces challenges in dealing with deepfakes.